(untitled) (International Journal of Scientific Trends, 2026)
Human beings are inherently social creatures, and social connection is a fundamental requirement for psychological well-being. This article examines the critical distinction between social isolation—defined as an objective lack of social contact—and loneliness, a subjective emotional experience arising from unmet social needs. The study analyzes various factors contributing to social disconnection, including family problems, physical disabilities, socioeconomic disadvantages, unemployment, and societal stigma. Research indicates that prolonged social isolation poses significant risks to mental health, increasing the likelihood of depression, anxiety, sleep disturbances, stress-related disorders, and cognitive decline. Particular attention is given to high-risk populations, such as older adults, adolescents, immigrants, and individuals affected by internalized or public stigma. Gender-based differences are also explored, suggesting that while males may experience higher measurable levels of social isolation, females in certain age groups report higher levels of loneliness. To mitigate these negative outcomes, the report proposes practical interventions, including the use of modern technology—such as social media and digital communication platforms—to maintain social ties and foster community engagement, as well as animal companionship, which can provide emotional support, enhance resilience, and reduce feelings of loneliness. Although eliminating social isolation entirely may be difficult, the implementation of evidence-based strategies and proactive social policies can significantly reduce its adverse impact on mental health and global public health outcomes.